2x=-44-3(2x+-4)

Simple and best practice solution for 2x=-44-3(2x+-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x=-44-3(2x+-4) equation:



2x=-44-3(2x+-4)
We move all terms to the left:
2x-(-44-3(2x+-4))=0
We add all the numbers together, and all the variables
2x-(-44-3(2x-4))=0
We calculate terms in parentheses: -(-44-3(2x-4)), so:
-44-3(2x-4)
determiningTheFunctionDomain -3(2x-4)-44
We multiply parentheses
-6x+12-44
We add all the numbers together, and all the variables
-6x-32
Back to the equation:
-(-6x-32)
We get rid of parentheses
2x+6x+32=0
We add all the numbers together, and all the variables
8x+32=0
We move all terms containing x to the left, all other terms to the right
8x=-32
x=-32/8
x=-4

See similar equations:

| u+41/9=8 | | 8x-4+5=2(2x+1)+3 | | 2x-2=5(x=1)=50 | | (5/3)x+(1/3)x=(10/3)+(7/3)x | | (c+3.6)4-2c=9.6 | | 9x+12x-21=27 | | y²=6y* | | y²=6y | | 8-2x=18-4x | | 5(x+8)=x+20 | | (x−1/2)/3=7 | | 8=14-3q | | 2(x-2)=x-5 | | 3/d-10=-2 | | -3^(2)-16=-3x | | -0.3.75c-11=13 | | -3^(2)-16=-x | | -15=3(-6x+5)+3 | | 5^x-2^x=10 | | 6x+3x+1x=180 | | 0.85x+5=15 | | 18x+5=100 | | 2/3x^2-15=0 | | 2+3∣10+x∣=23 | | w+19=22 | | 4d-2=14 | | 56-9x=24-x | | 9x+24=x+16 | | -3+-4x=15 | | -8−6y=-5y | | 5x-3-2x=9-3x+4 | | 115x-3(3x+4)=6 |

Equations solver categories